Activity antibacterial from honey kelulut (Trigona sp.) against bacteria Staphylococcus epidermidis - Sita, Annisa Aulia; Rijai, Laode; Rija'i, Hifdzur Rashif (Journal of Pharmaceuticals and Natural Sciences, 2024)
Honey kelulut is derived from the kelulut bee (Trigona sp.), which is native to Kalimantan and belongs to the Trigona genus of stingless bees. The honey produced by the Trigona genus has a well-documented antibacterial property. Study objective accomplished. This text discusses the potent antibacterial action of kelulut honey. The antibacterial testing method employed is the well diffusion method, utilizing the bacterium Staphylococcus epidermidis as the test organism. An antibacterial test was conducted by measuring the diameter of the zone of inhibition against bacteria. The results were obtained from concentrations of 40%, 60%, 80%, and 100%. Then the resistance diameter was measured for each concentration. The most optimal outcomes were achieved in the antibacterial test using honey kelulut. The honey kelulut with an 80% concentration exhibited a medium resistance level of 10.2 mm, while the 100% concentration demonstrated a strong resistance level of 13.7 mm.